Analisis Faktor Pemakaian Jasa Bantuan Hukum Probono Legal Aid di Pengadilan Agama Kelas 1A Tanjung Karang Kota Bandar Lampung - Zaelani, Abdul Qodir (AL-ISTINBATH : Jurnal Hukum Islam, 2020)
The purpose of this study is to uncover the factors underlying the use of probono legal aid legal aid services in the Class 1A Religious Court of Tanjung Karang, Bandar Lampung City. This research is a field research (field research), primary data taken from service users, service managers and officials in the Class 1A Religious Court of Tanjung Karang in Bandar Lampung City, through structured free interviews. This research found the fact that the presence of Legal Aid Posts which provide probono legal aid services is very helpful for people who need legal assistance because of their limitations with the factors that become the reasons for using legal aid services for probono legal aid. For those who do not understand the law, the presence of Posbakum in the Class 1A Religious Court of Bandar Lampung City is very helpful in the process of resolving legal issues, as well as for those who do not have sufficient budget and funds to resolve legal issues that are being passed through, the presence of Posbakum is very helpful and reduce their financial expenses. The presence of Posbakum also facilitates and accelerates the resolution of legal issues.